2013
DOI: 10.1016/j.microc.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A simple dilute-and-shoot procedure for Si determination in diesel and biodiesel by microwave-induced plasma optical emission spectrometry

Abstract: In the present work, microwave-induced plasma optical emission spectrometry (MIP OES) and the flow blurring nebulizer (FBN) technology are used to determine silicon in diesel and biodiesel samples. A simple diluteand-shoot procedure with ethanol is presented. Two additional sample preparation procedures are also evaluated for comparison: closed-vessel microwave-assisted acid digestion and microemulsion preparation in n-propanol. Limits of detection (LOD) vary from 5 to 20 μg L −1 and relative standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…The measurement of S by traditional ICP-MS suffers severer spectral interferences by 16 Optimization of the flow rate of O2 was carried out to achieve the best DL for 32 S + . The results of the signal intensity, BEC, and DL are plotted in Figs.…”
Section: Optimization Of the O2 Flow Rate As The Reaction Gas For Meamentioning
confidence: 99%
See 3 more Smart Citations
“…The measurement of S by traditional ICP-MS suffers severer spectral interferences by 16 Optimization of the flow rate of O2 was carried out to achieve the best DL for 32 S + . The results of the signal intensity, BEC, and DL are plotted in Figs.…”
Section: Optimization Of the O2 Flow Rate As The Reaction Gas For Meamentioning
confidence: 99%
“…Alternatively, simple dilution with organic solvents had been reported to be effective for the determination of the elements in fuel samples. [15][16][17] De Souza et al had reported that xylene dilution was useful for multielemental determinations in oil matrices by ICP-MS with a dynamic reaction cell. 17 Such organic solvent dilution methods are candidate high-throughput sample pretreatment methods for determining the elements in a BDF sample because the operations are very simple and could be carried out in a shorter time (several minutes).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, an attempt was made to demonstrate the potential of MP-AES for environmental studies [20]. Several other studies have employed MP-AES for the determination of trace elements such as Cu, Fe, Mn, and Zn in animal feed and fertilizers [21], gasoline and ethanol [22], petroleum crude oil [23], diesel and biodiesel [24], and biofortified yeast analysis [25]. Different procedures have been proposed for determining the content of metallic species in biosludge samples [26].…”
Section: Introductionmentioning
confidence: 99%